Reception Analysis of Millennials Generation to Ads in Social Media - Setiya Hertanti Oktayusita; Basuki Agus Suparno; Christina Rochayanti (Jurnal Ilmu Komunikasi, 2019)
Gerindra presented an ad under the title of “Indonesia Bergerak Bersama Gerindra dan Rakyat version Sarjana Kerja Kerja Kerja!”, but due to the use of symbols and visualization, it became viral and caused controversy in the community. This study aims to determine the opinion of millennials response after watching the ads. The research is qualitative research approach used is the analysis of the reception, the technique of collecting data is using interviews, observation and document analysis. The theory used to analyze the meaning of the audience is the encoding-decoding, reception analysis theory and new media theory. The result of this study indicate three position of millennials reception, namely a dominant, negotiated, and oppositional position. In the dominant position, it’s considered as a good political ad because it successfully criticizes the government by presenting the reality of the existing problems. In the negotiating position, millennials saw the ads containing a message of criticism without a solution, in this condition millennials refused some symbols such as the use of profession symbols and titles in it, while in the opposition position, millennials considered the ads irrelevant and interpret it as a black campaign. There are several factors that become the benchmark of the millennials in perceiving that ads in social media like the character of millennials, education background, job, experience and view or tendencies to political parties. This research contributes in the form of policy recommendations to the Gerinda Party to pay more attention to solutions to criticism of advertising so as not to cause new problems.